JEWISH SCHOOLS IN IRAQ, 1864– 1952 (Journal of the College of Education for Women, 2019)
1- That the Jewish minority, was considered one of Iraq`s 1864-1952 main religious minorities ,and has the therights by the Iraqi constitution approved by the Iraqi peopel in addition to the items all ocated py the minorities includiny the Jewish minority .He also bledged formaly before the Nations council to get its independence and to respect the rights of minorities . 2- The Jews who have completed primary education in Jweish and government schools Increased the number so that it seemed that the percentage of illiterate males was zero and the female was not high and as aresult of the increasing number of primary school graduates, so it was need to open addition secondary schools, also increased the number of high school graduates from the Jews, it was increased in number of graduation from secondary school . 3- We can deduce from the foregoing that the interest of the British after the occupation of Iraq, the Jews and the high level of education in schools, and their emphasis on the study of foreign languages, this interest was not available in schools, the Iraqi government . 4- teachers had an important role in establishing the principles and targest of zionism and the role of Jewish schools for education of yong Jewish Zionist Education . 5- The creation of Israel in 1948 was that offended the Jews of Iraq scattered and attracted and thir numbers are rising , especially between (1950-1951) . 6- the Jews had played great role in particption the Iragi in establish the defrent Iragi organization and that was ensured into the real living between them and the Iraq is people .